Do undergraduate general practice placements propagate the 'inverse care law'?. Issue 5 (3rd September 2022) - Butler, Daniel; O'Donovan, Diarmuid; McClung, Alice; Hart, Nigel
ABSTRACT: Introduction: Fifty years since Dr Tudor-Hart's publication of the 'Inverse Care Law', all-cause mortality rates and COVID-19 mortality rates are higher in more deprived areas. Part of the solution is to increase access and availability to healthcare in underserved and deprived areas. This paper examined how socio-economically representative the undergraduate general practice placements are in Northern Ireland (NI). Methods: A quantitative study of general practices involved in undergraduate medical placements through Queen's University Belfast, comparing practice lists by deprivation indices, examining both blanket deprivation and deprivation quintile trends for teaching and non-teaching practices. Results: Deprivation data for 135 teaching practices were compared against the 323 NI practices. Teaching practices had fewer patients living in the most deprived quintiles compared with non-teaching practices. Fewer practices with blanket deprivation were involved in undergraduate medical education, 32% compared with 42% without blanket deprivation. Practices in areas of blanket deprivation were under-represented as teaching practices, 10%, compared to 14% of NI general practices that met this criterion. Conclusion: Practices with blanket deprivation were under-represented as teaching practices. Exposure to general practice in deprived areas is an essential step to improving future workforce recruitment and ultimately to closing the health inequalities gap. Ensuring practices in high-need areas are proportionately represented in undergraduate placements is one way to direct action in addressing the 'Inverse Care Law'. This study is limited to NI and further work is required to compare institutions across the UK and Ireland.